Influence of Antihypertensive Treatment on RAAS Peptides in Newly Diagnosed Hypertensive Patients - Annina S. Vischer; Gabriela M. Kuster; Raphael Twerenbold; Otmar Pfister; Qian Zhou; Andrea Villiger; Marko Poglitsch; Stephan Krähenbühl; Michael Mayr; Stefan Osswald; Manuel Haschke; Thilo Burkard (Cells, 2021)
(1) Background: Recently, influences of antihypertensive treatment on the renin–angiotensin–aldosterone system (RAAS) has gained attention, regarding a possible influence on inflammatory and anti-inflammatory pathways. We aimed to study the effects of newly initiated antihypertensive drugs on angiotensin (Ang) II and Ang (1–7) as representers of two counter-regulatory axes. (2) Methods: In this randomized, open-label trial investigating RAAS peptides after the initiation of perindopril, olmesartan, amlodipine, or hydrochlorothiazide, Ang II and Ang (1–7) equilibrium concentrations were measured at 8 a.m. and 12 a.m. at baseline and after four weeks of treatment. Eighty patients were randomized (1:1:1:1 fashion). (3) Results: Between the four substances, we found significant differences regarding the concentrations of Ang II (p < 0.0005 for 8 a.m., 12 a.m.) and Ang (1–7) (p = 0.019 for 8 a.m., <0.0005 for 12 a.m.) four weeks after treatment start. Ang II was decreased by perindopril (p = 0.002), and increased by olmesartan (p < 0.0005), amlodipine (p = 0.012), and hydrochlorothiazide (p = 0.001). Ang (1–7) was increased by perindopril and olmesartan (p = 0.008/0.002), but not measurably altered by amlodipine and hydrochlorothiazide (p = 0.317/ 0.109). (4) Conclusion: The initiation of all first line antihypertensive treatments causes early and distinct alterations of equilibrium angiotensin levels. Given the additional AT1R blocking action of olmesartan, RAAS peptides shift upon initiation of perindopril and olmesartan appear to work in favor of the anti-inflammatory axis compared to amlodipine and hydrochlorothiazide.